2017
DOI: 10.1093/occmed/kqx091
|View full text |Cite
|
Sign up to set email alerts
|

Job demands, resources and mental health in UK prison officers

Abstract: The findings of this study can help occupational health practitioners and psychologists develop structured interventions to improve well-being among prison officers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 21 publications
2
40
1
2
Order By: Relevance
“…Shift working, night shifts, overstaying breaks and shift ends, workload, ‘corridor medicine’ are all significant factors influencing wellbeing. 2426 Recognition of these factors and how the pandemic will influence them is important. The pandemic will also probably cause changes to other factors that affect wellbeing such as the structure of the organisation, roles of staff, autonomy and availability of senior support.…”
Section: What Can Organisations Do For Staffmentioning
confidence: 99%
“…Shift working, night shifts, overstaying breaks and shift ends, workload, ‘corridor medicine’ are all significant factors influencing wellbeing. 2426 Recognition of these factors and how the pandemic will influence them is important. The pandemic will also probably cause changes to other factors that affect wellbeing such as the structure of the organisation, roles of staff, autonomy and availability of senior support.…”
Section: What Can Organisations Do For Staffmentioning
confidence: 99%
“…Such moral distress has consequences for healthcare organisations as it can negatively influence staff morale, confidence, sense of purpose, integrity, and respect for the organisation (Nelson 2009 ). It also has implications for the wider healthcare service as the higher the level of moral distress, the greater the likelihood of leaving a position (Hamric and Blackhall 2007 ; Oliver 2018 ), which is significant in the UK where we are informed that there are insufficient healthcare professionals to cope with patient demand (British Medical Association 2018 ; Kinman and Teoh 2018 ), and challenges exist around staff recruitment and/or retention in certain healthcare specialities (British Medical Association 2017 ; Chaudhuri et al 2013 ). In the UK, the General Medical Council are conducting a review of the wellbeing of medical students and healthcare staff, and attempts are being made to support NHS staff through the provision of reflective spaces (see, e.g., Gannon 2014 ) as recognition increases of the emotional burden that staff carry in their daily work (see, e.g., Cornwell and Fitzsimons 2017 ; Kerasidou and Horn 2016 ;).…”
Section: The Need For Shifting Perceptions When Writing a Business Camentioning
confidence: 99%
“…In general, prison staff themselves are at a higher risk of psychological distress than the general population (Harvey, 2014;Kinman et al, 2017). In terms of protective factors, Harvey (2014) determined that staff accessing support in the prison was helpful.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of protective factors, Harvey (2014) determined that staff accessing support in the prison was helpful. In relation to emotional support, Kinman et al (2017) found working relationships and role clarity were helpful for staff but managerial support was not (Kinman et al, 2016). Lack of support has been associated with prison officer stress and burnout (Finney et al, 2013;Holmes & MacInnes, 2003).…”
Section: Introductionmentioning
confidence: 99%